ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHATANI JAGUNG MANIS HIBRIDA DI DESA BOCEK KECAMATAN KARANGPLOSO KABUPATEN MALANG JAWA TIMUR - Fitriandani Fitriandani; Dr.Dwi Susilowati; Ir.Sri Hindarti (Program Studi Agribisnis, 2020)
This study aims to determine the efficiency of farming and the factors affecting farm income of hybrid sweet corn farming in Bocek Village, Karangploso District. The study was conducted in Bocek Village, Karangploso District, Malang Regency by using purposive random sampling using 30 samples of hybrid sweet corn farmers. Analysis of the data used is farm efficiency analysis and regression analysis of multiple regression analysis models. The results of this study t-test showed that the variable seed, labor, and pearl fertilizer significantly affected the income of hybrid sweet corn farming with a significant value of 0.05 <5% and for the variables of pesticides, urea fertilizer, za fertilizer, phonska fertilizer, and manure not affect the income of hybrid sweet corn farming. And based on the results of the analysis it can be seen that the average acceptance of each respondent is Rp.36,864,375/ha. The total production cost was obtained from the sum of Rp.19,834,375/ha with a total variable cost of Rp.18,775,426/ha, so that the total production cost was Rp.19,834,375/ha. Income is obtained from the average revenue minus total production costs, so that income is 17,030312/ha.Keywords: Hybrid Sweet Corn, Farming, Income